Diagnostics of soil management problems with organic fertilizers using a miniature rain simulator - Sarasty B., Jairo; Ortega M., Jimmy Andrés; Castillo F., Jesús Antonio; Chaves-Jurado., Germán (Revista de Ciencias Agrícolas, 2017)
The study was conducted in the hillside area of the departamento de Nariño, Colombia, in a Pachic Fulvudands soil, under an Allium fistulosum L. crop with organic fertilizers for more than ten years; a completely randomized design in a trifactorial arrangement (3x4x6) was used, where the first factor corresponded to three terrain slopes (10°, 15°, and 25°), the second factor to the land uses with Allium fistulosum L. crop, under the application of three organic fertilizers (U1: Hen manure, U2: Bovine manure, U3: vegetable Residues) and a control U4 (Area in conservation with trees): the third factor corresponds to the simulation times by using a rain minisimulator (5, 10, 15, 20, 25 and 30 min). Throughout the experiment, a rainfall intensity of 15.5mm/h was applied as a result of the calibration according to the daily rainfall data from the zone. The results showed that the soil with bovine manure U2 had the highest values for runoff sheet (1.01, 2.51 and 4.96 mm) for the three slopes suggesting higher removal of surface particles from the soil. For the infiltration sheet, the highest values correspond to U4, with 7.18, 6.85, and 6.97mm, respectively, unlike U2 which presented the lowest average values and the highest soil losses with 0.072, 0.284, and 0.955 t.ha-1 in the three slopes. The results suggest that the addition of organic amendments together with soil management, in the long run, are not enough to reduce risks due to physical soil degradation.